Notices and Examples of Inscriptions on Old Castles and Town Houses in the North-east of Scotland - Jervise, Andrew (Proceedings of the Society of Antiquaries of Scotland, 1863)
This article discusses inscriptions found in the stonework of Scottish buildings from the sixteenth to the eighteenth centuries. The authors list several examples of inscriptions from across Scotland written in English, Latin, Greek and Hebrew. They also describe some of the decorative elements that occur near these inscriptions.